'Dramatic tone' as the emotional core of a screenplay: The case of The Diving Bell and the Butterfly (2007). (1st March 2017) - Braga, Paolo
This article delves into the topic of the central emotion within a screenplay, and the extent to which it can grant the work coherence. It will demonstrate that the emotional core of the story consists in the profound, extended emotion that stems directly from its main theme. It will make these arguments by analysing the screenplay for Julian Schnabel's The Diving bell and the Butterfly (2007), the screen adaptation of Jean-Dominique Bauby's memoir regarding his experience of 'locked-in' syndrome. As Ronald Harwood's screenplay changes the thematic focus of the original novel, comparing the two texts reveals how different themes invoke different fundamental emotions. The article, drawing especially on the narrative theory developed in the screenwriting textbooks by Robert McKee (1997) and John Truby (2007), elaborates on an issue that has been ignored by other analyses of the movie: from the open-ended story of self-reflection that is told in the book, Harwood gets a closeended story of rebirth. The article highlights how the tension towards the protagonist's internal goal determines the emotional nucleus of the plot. It also suggests that the emotional core is informed by 'dramatic tone' and argues that it consists in the 'desire of justice' regarding the main character's destiny.